Learning through Online Engagement Amidst Covid-19 Pandemic: Exploring Students’ Perceptions, Opportunities and Challenges - Jyoti, Rameshwar (Butwal Campus Journal, 2022)
This study aims at exploring how M Ed English (Master of Education) students perceive online learning amidst the COVID-19 pandemic. The study has adopted online collaborative learning theory (OCL) as a theoretical stance for the study and employed a qualitative research design as a research method. Six M Ed students have been purposively selected as research participants, who were learning English in online environment during the COVID-19 pandemic. They were selected from two TU affiliated campuses located in Rupandehi district. In order to collect the data, a semi-structured interview technique has been used. The study uncovers that M Ed English students perceive online learning as an alternative way of learning during pandemic situation. It further depicts that through online learning, students improve their language skills, collaborative practices, and digital literacy. Besides these, the study demonstrates that inadequate skills of ICT in teachers and students, lack of internet and smart digital gadgets, learning anxiety, lack of peace zone at home are some challenges in online learning. The study contributes to the students’ understanding of learning through online mode.